2006
DOI: 10.4067/s0716-97602006000500005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and antioxidant status in blood of patients with uterine myoma, endometrial polypus, hyperplastic and malignant endometrium

Abstract: Oxidative stress is considered to be involved in pathogenesis of many disorders of the female genital tract. In this study, we explored the lipid peroxidation levels and antioxidant enzyme activities in women diagnosed with different forms of uterine diseases in order to evaluate the extent of oxidative stress in blood of such patients. Blood samples of healthy subjects and gynecological patients were collected and subjected to assays for superoxide dismutase, catalase, glutathione peroxidase, glutathione redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
24
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 32 publications
10
24
1
Order By: Relevance
“…These results were also in agreement with other investigations done by Pejic et al, 2006, which showed an increase in concentration of lipid peroxidation products, as markers of oxidative stress whereas the level of antioxidants decreased in uterine cancer patients. The rise in MDA concentration could be due to increased generation of ROS due to the excessive oxidative damage generated in uterine cancer patients, oxygen radical production, which increases with clinical progression of diseases, involves increased lipid peroxidation, as a result of which there are cellular membrane degeneration and DNA damages 6 (Naidu MSK, et al 2007).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results were also in agreement with other investigations done by Pejic et al, 2006, which showed an increase in concentration of lipid peroxidation products, as markers of oxidative stress whereas the level of antioxidants decreased in uterine cancer patients. The rise in MDA concentration could be due to increased generation of ROS due to the excessive oxidative damage generated in uterine cancer patients, oxygen radical production, which increases with clinical progression of diseases, involves increased lipid peroxidation, as a result of which there are cellular membrane degeneration and DNA damages 6 (Naidu MSK, et al 2007).…”
Section: Discussionsupporting
confidence: 83%
“…The oxygen radical production increases with clinical progression of diseases and involves increased lipid peroxidation. As a result of this, there are cellular membrane degeneration and DNA damage 9 (Pejic, et al 2006). The rise in the levels of MDA indicate excessive lipid peroxidation as a consequence of the increase in free radical generation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased levels of Cat and prolidase enzyme activity in the serum of the fi broid group with respect to the control group were remarkable. Pejic et al (2006) had studied oxidant and antioxidant parameters in the serum of the patients with uterine myoma, endometrial polyps, hyperplastic and malignant endometrium and found elevated serum levels of LOOH in the uterine myoma patients compared to the control group. On the contrary, we could not fi nd a signifi cant diff erence in the serum LOOH levels between the study and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Pejić and collaborators observed that perturbation of antioxidant status is more pronounced in blood of patients with premalignant (hyperplastic) and malignant (adenocarcinoma) lesions, compared to those with benign uterine changes such as polypus and myoma [ 78 ]. Although information about the role of different signaling pathways highlight the role of proteins in the onset and development of myomas, comparative proteome profi ling studies are still lacking.…”
Section: Perspectivesmentioning
confidence: 99%